Old industrial cities seeking new road of industrialization : Models of revitalizing Northeast China - Wang, Mark; Chen, Zhiming; Zhang, Pingyu; Tong, Lianjun; Ma, Yanji (World Scientific Publishing Company, 2014)
This book explores how cities in China's rust belt, particularly in northeast China, are restructuring their industries and economies after decades of decline. Once the heart of China's industrialization, the region suffered under market reforms and competition from coastal areas. Since the 2003 "Revitalisation Strategy," these cities have undergone significant transformation. The authors identify six distinct reindustrialization models that illustrate different paths toward economic renewal and sustainable growth.